Profit-Loss Sharing in Islamic Banking: Global Insights from a Systematic Review - Fahamsyah, Mohammad Hatta; Laila, Nisful; Rakhmat, Adrianna Syariefur; Shabbir, Malik Shahzad (Economica: Jurnal Ekonomi Islam, 2023)
Islamic banking emerged as a response to the limitations of interest-based financial systems, offering alternative models rooted in Shariah principles—chief among them the profit-and-loss sharing (PLS) mechanism. This study re-examines the implementation of PLS in Islamic banks, identifying key challenges and outlining directions for future research within the framework of Shariah-compliant financial practices. Employing a systematic literature review of Scopus-indexed journal articles, the study compares theoretical foundations and empirical evidence surrounding PLS applications in contemporary Islamic banking. Findings indicate that PLS practices remain only partially aligned with Shariah principles, constrained by insufficient regulatory oversight, heightened credit risk, and moral hazard concerns. The study also identifies critical gaps in community awareness and operational management, underscoring the need for product innovation, stronger governance structures, and targeted educational initiatives. These insights point to three strategic priorities for stakeholders: enhancing governance to mitigate moral hazards, integrating macroeconomic policy support to improve PLS scalability, and expanding public education to close knowledge gaps. Together, these measures can support a more sustainable, equitable, and competitive Islamic banking sector.